"How Do I Carry All This Now?" Understanding Consumer Resistance to Sustainability Interventions. (May 2021) - Gonzalez-Arcos, Claudia; Joubert, Alison M.; Scaraboto, Daiane; Guesalaga, Rodrigo; Sandberg, Jörgen
Given the increasingly grave environmental crisis, governments and organizations frequently initiate sustainability interventions to encourage sustainable behavior in individual consumers. However, prevalent behavioral approaches to sustainability interventions often have the unintended consequence of generating consumer resistance, undermining their effectiveness. With a practice–theoretical perspective, the authors investigate what generates consumer resistance and how it can be reduced, using consumer responses to a nationwide ban on plastic bags in Chile in 2019. The findings show that consumer resistance to sustainability interventions emerges not primarily because consumers are unwilling to change their individual behavior—as the existing literature commonly assumes—but because the individual behaviors being targeted are embedded in dynamic social practices. When sustainability interventions aim to change individual behaviors rather than social practices, they place excessive responsibility on consumers, unsettle their practice-related emotionality, and destabilize the multiple practices that interconnect to shape consumers' lives, ultimately leading to resistance. The authors propose a theory of consumer resistance in social practice change that explains consumer resistance to sustainability interventions and ways of reducing it. They also offer recommendations for policy makers and social marketers in designing and managing sustainability initiatives that trigger less consumer resistance and thereby foster sustainable consumer behavior.